Use of ICT by students at the Faculty of Humanities and Social Sciences in Zagreb, Croatia - Vrana, Radovan (2011)
In Croatia, ICT has become the integral part of educational process on all levels of education including the higher education. Students at universities are exposed to the use of ICT during their formal education, and this exposure requires constant acquisition of new knowledge which would help them to become and remain competent ICT users. With the greater availability of ICT, students’ habits, and methods of use of ICT change. Findings of the research carried out among students at the Faculty of Humanities and Social Sciences in Zagreb, Croatia about use of ICT, showed that students use personal computer and the internet mostly for their education and also for other non education related activities such as communication with family and friends, watching videos, listening to the music etc. Findings also showed that they learn about use of ICT mostly by themselves and that they are already experienced users of the internet which they use moderately. Use of ICT by students in this research confirmed that they have truly embraced ICT not only for their education but also for other purposes.
Projekt MZOS
ENG